A Retrospective Analysis of BCR-ABL1 Kinase Domain Mutations in the Frontline Drug Intolerant or Resistant Chronic Myeloid Leukemia Patients: An Indian Experience from a High-End Referral Laboratory - Majumdar, Atreye; Katara, Rahul; Mishra, Avshesh; Gupta, Aastha; Sharma, Deepak K.; Srivastava, Aman K.; Sharma, Shivani; Jaiswal, Ankita; Dixit, Mallika; Kumar, Vipin; Kumar, Sachin; Kumar, Varun; et al. (South Asian journal of cancer, 2024)
Objective This article identifies and evaluates the frequency of mutations in the BCR-ABL1 kinase domain (KD) of chronic myeloid leukemia (CML) patients who showed suboptimal response to their current tyrosine kinase inhibitor (TKI) regime and assesses their clinical value in further treatment decisions. Materials and Methods Peripheral and/or bone marrow were collected from 791 CML patients. Ribonucleic acid was extracted, reverse transcribed, and Sanger sequencing method was utilized to detect single-nucleotide variants (SNVs) in BCR-ABL1 KD. Results Thirty-eight different SNVs were identified in 29.8% (n = 236/791) patients. T315I, E255K, and M244V were among the most frequent mutations detected. In addition, one patient harbored a novel L298P mutation. A subset of patients from the abovementioned harbored compound mutations (13.3%, n = 33/236). Follow-up data was available in 28 patients that demonstrated the efficacy of TKIs in correlation with mutation analysis and BCR-ABL1 quantitation. Molecular response was attained in 50% patients following an appropriate TKI shift. A dismal survival rate of 40% was observed in T315I-harboring patients on follow-up. Conclusion This study shows the incidence and pattern of mutations in one of the largest sets of Indian CML patients. In addition, our findings strengthen the prognostic value of KD mutation analysis among strategies to overcome TKI resistance.